Status Of Corruption Acts Under The Indonesian Criminal Law System - Ahmad Nur Azizy; Budi Parmono; Moh. Muhibbin (Scholar Center, 2023)
The purpose of this research is to describe the regulation of criminal law in Indonesia and to analyze the position of corruption in Indonesian criminal law. This research uses normative legal research in the form of library research using three types of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials, with the nature of qualitative descriptive research. The results of the study show that the criminal act of corruption is a part of Indonesian criminal law whose arrangements are outside the Criminal Code (KUHP). In addition, this crime has certain specifications that are different from general criminal law which are regulated in separate laws, namely: Law Number 31 of 1999 as amended in Law Number 20 of 2001 concerning Eradication of Corruption Crimes. The criminal act of corruption is also known as a special crime. The criminal act of corruption is a part of the special criminal law which has certain specifications that are different from the general criminal law, such as deviations from procedural law and when viewed from the regulated material. The Criminal Procedure Code for corruption that is applied is lex specialist in nature, namely the existence of deviations intended to speed up procedures and obtain investigations, prosecutions and examinations at court hearings.